Bis(pyrazolyl)methanetetracarbonyl-molybdenum(0) as precursor to a molybdenum(VI) catalyst for olefin epoxidation - Figueiredo, Sónia (2013)
Bis(pyrazolyl)methanetetracarbonyl-molybdenum(0), cis-[Mo(CO)4(BPM)] (1), was prepared from Mo(CO)6 and the ligand bis(pyrazolyl)methane (BPM), and examined as a catalyst precursor for the epoxidation of olefins using tert-butylhydroperoxide (TBHP) as oxidant. Catalytic activities followed the sequence 1-octene < trans-2-octene < a-pinene < (R)-(þ)-limonene < cis-cyclooctene, and, with the exception of a-pinene and limonene, the corresponding epoxide was always the only reaction product. Turnover frequencies for the epoxidation of cyclooctene were 580 mol molMo 1 h 1 at 55 C and 1175 mol molMo 1 h 1 at 75 C, which compare favourably with those found for other molybdenum carbonyl complexes used as catalyst precursors for the same reaction under similar conditions. Catalytic activities were lower in the presence of organic co-solvents, decreasing in the sequence 1,2-dichloroethane > nitromethane > ethanol > hexane > acetonitrile. It is proposed that the oxodiperoxo complex [MoO(O2)2(BPM)] (2) may be the active catalyst formed in situ by oxidative decarbonylation of 1, since crystals of 2 suitable for structure determination by X-ray diffraction were obtained from the reaction solution recovered after a catalytic run at 55 C with cis-cyclooctene as substrate. In support of this hypothesis, the catalytic performance of 2 for the epoxidation of cyclooctene at 55 C is very similar to that for 1.